Cultural Contents in Digital Authentic Greeting Cards as English Teaching Materials for Junior High Schools - Angelina, Shely; Mayuni, Ilza; Agustina, Imas Wahyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2022)
This study aimed to discover the cultural contents in the digital authentic greeting cards as English teaching materials for junior high schools. The research data were the cultural values in the form of words, phrases, clauses, or sentences that are contained in the texts on the digital authentic greeting cards. The data sources were taken from several websites providing free digital greeting cards to be downloaded. The data were analyzed with the framework of the cultural dimensions by Moran (2001) and the cultural sources by Chao (2011) by using a qualitative content analysis method. The findings revealed 101 cultural contents that were classified into the four cultural dimensions and three sources of culture. The cultural contents were mostly identified in the Universality across Culture and represented by the Practices dimension through activities and language expressions. It was indicated that a large proportion of the cultural contents were included in universal contents that are not specific to any particular country and were represented by actions and interactions carried out by the cultural members.